(untitled) (Orfeu, 2020)
In this text, which was written in a back-and-forth flow, almost a metaphor for the compositional process that he narrates, I tried to put on a list of recurring compositional procedures in my creative work, which has as its starting point the bird song and simple models as a principle of melodic and rhythmic and even harmonic genesis. In its core, I present the theoretical foundation in a poetic reading (related not to philosophy or theories, but to models of creation), based on the Alagmatics proposed by Gilbert Simondon in his book L’individuation à la lumière des notions de forme et d ‘information and Imagination et Invention. In this way, I seek to think of musical continuity among heterogeneous individuals by local consistency, as an alternative to the traditional notion of logical and ideal unity among homogeneous ones.